MonTI 2020
DOI: 10.6035/monti.2020.12.12
|View full text |Cite
|
Sign up to set email alerts
|

New taxonomy of easy-to-understand access services

Abstract: The Convention on the Rights of People with Disabilities states that access to information through written and electronic communications is essential for personal development and full participation in society. In digital scenarios, media services, such as audio descriptions, subtitles, or sign language, facilitate access to content with a focus on sensory barriers. Still, there are shortcomings in addressing other needs, such as cognitive ones. This article aims to suggest a taxonomy of the emerging easy-to-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…24 Geert Freyhoff et al, Make it Simple: European Guidelines for the Production of Easy-to-Read Information for People with Learning Disability for Authors, Editors, Information Providers, Translators and Other Interested Persons, 1998, Cascais, ILSMH European Association, s. 7. w zakresie tworzenia łatwych do zrozumienia informacji, przede wszystkim treści audiowizualnych. W najnowszych badaniach wyłaniają się takie zagadnienia, jak: łatwa audiodeskrypcja 25 czy łatwa do zrozumienia audiodeskrypcja 26 . Naukowcy analizują między innymi możliwości wykorzystania zasad łatwego języka w celu uproszczenia audiodeskrypcji, a hipotezą ich badań jest to, że "audiodeskrypcja, która jest łatwiejsza do słuchania i zrozumienia, będzie lepiej rozumiana przez odbiorców, a także łatwa do słuchania i łatwa do zrozumienia audiodeskrypcja przyczyni się do upowszechnienia AD" 27 .…”
Section: Sztuka Dostępna Dla Niewidomych I Niedowidzących Odbiorców W...unclassified
See 1 more Smart Citation
“…24 Geert Freyhoff et al, Make it Simple: European Guidelines for the Production of Easy-to-Read Information for People with Learning Disability for Authors, Editors, Information Providers, Translators and Other Interested Persons, 1998, Cascais, ILSMH European Association, s. 7. w zakresie tworzenia łatwych do zrozumienia informacji, przede wszystkim treści audiowizualnych. W najnowszych badaniach wyłaniają się takie zagadnienia, jak: łatwa audiodeskrypcja 25 czy łatwa do zrozumienia audiodeskrypcja 26 . Naukowcy analizują między innymi możliwości wykorzystania zasad łatwego języka w celu uproszczenia audiodeskrypcji, a hipotezą ich badań jest to, że "audiodeskrypcja, która jest łatwiejsza do słuchania i zrozumienia, będzie lepiej rozumiana przez odbiorców, a także łatwa do słuchania i łatwa do zrozumienia audiodeskrypcja przyczyni się do upowszechnienia AD" 27 .…”
Section: Sztuka Dostępna Dla Niewidomych I Niedowidzących Odbiorców W...unclassified
“…Recent studies have revealed such issues as easy audio description 25 and easy-to-understand audio description. 26 Among other things, researchers have been analysing the possibility of using the principles of easy language to simplify audio description and they have formulated a hypothesis that "an audio description that is easier to listen to and understand will elicit a better audience comprehension performance and AD which is easy to listen to and easy to understand would contribute to mainstreaming AD". 27 They demonstrate that such easy AD would come down to "reduction in the volume and complexity of information and language materials, in order to produce an immediate, clear, empathetic and concise communication".…”
Section: Audio Descriptionmentioning
confidence: 99%
“…Despite their opposing views, scholars from both approaches and non-academic experts agree that further research is needed for bridging existing gaps. For instance, the need for reception studies with eye-tracking [38], for sound knowledge about the target audiences [39], for reception studies in easy audiovisual content [40], empirically-based guidelines [2,13], the systematisation of validation process [8,35], or the need for harmonised training across Europe [19]. The latter is one of the goals of the Train2Validate project.…”
Section: Research Backgroundmentioning
confidence: 99%